Writing performance in EFL at a college level using peer editing - Cárdenas Sánchez, Silva Elizabeth; Naranjo Lozada, Ximena Elizabeth (Machala : Editorial UTMACH, 2020)
Today, people are learning more and more languages for different reasons. To learn a language includes the development of all the skills in order to comprehend oral and written material. English, which is a universal language, is one of those languages, and it is used in different fields to promote communication. Thus, this paper focuses on one of the most important skills, which is writing. In a setting where English is taught as a Foreign Language (EFL), it is essential to learn how to write correctly following the language standards. With this in mind, the following research is framed in a context where college students developed the writing skill through paragraphs and peer correction. Students were instructed in different writing topics and peer correction.
Keywords: PEER EDITING; COOPERATIVE LEARNING